2017
DOI: 10.3389/fphys.2017.00347
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Adaptations to Hypoxic vs. Normoxic Training during Intermittent Living High

Abstract: In the setting of “living high,” it is unclear whether high-intensity interval training (HIIT) should be performed “low” or “high” to stimulate muscular and performance adaptations. Therefore, 10 physically active males participated in a 5-week “live high-train low or high” program (TR), whilst eight subjects were not engaged in any altitude or training intervention (CON). Five days per week (~15.5 h per day), TR was exposed to normobaric hypoxia simulating progressively increasing altitude of ~2,000–3,250 m. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 105 publications
1
32
0
1
Order By: Relevance
“…In contrast, the non-significant changes of the muscle strength of the arms were not higher than the measurement error (elbow flexion: ∼6%, elbow extension: ∼8%; see Törpel et al, 2017) and must therefore considered to be insubstantial. In comparison to previous RTH studies using low to moderate loads, the amount of these improvements are comparable (Manimmanakorn et al, 2013a,b;de Smet et al, 2017) or higher (Friedmann et al, 2003). Regarding muscle strength capacity, the RTH-interventions using a moderate to high load achieved comparable (Mayo et al, 2018), higher (*corrected p-value by using the Bonferroni-Holm method -the correction factor corresponds to the number of the tests [time × group effect] within the parameter groups; maximal respiratory exchange ratio: RER max , peak oxygen uptake: VO2 peak , oxygen uptake at one watt per kilogram: VO2 1W/kg , maximal power output: PO max , power output at the second lactate threshold: PO LT2 , heart rate at one watt per kilogram: HR 1W/kg , maximal muscular strength: F max for the exercises elbow extension and flexion/knee extension and flexion, total hemoglobin mass: tHb, blood volume: BV, fat mass: FM, fat free mass: FFM).…”
Section: Effects Of Rth On Muscle Strength Capacitysupporting
confidence: 60%
See 3 more Smart Citations
“…In contrast, the non-significant changes of the muscle strength of the arms were not higher than the measurement error (elbow flexion: ∼6%, elbow extension: ∼8%; see Törpel et al, 2017) and must therefore considered to be insubstantial. In comparison to previous RTH studies using low to moderate loads, the amount of these improvements are comparable (Manimmanakorn et al, 2013a,b;de Smet et al, 2017) or higher (Friedmann et al, 2003). Regarding muscle strength capacity, the RTH-interventions using a moderate to high load achieved comparable (Mayo et al, 2018), higher (*corrected p-value by using the Bonferroni-Holm method -the correction factor corresponds to the number of the tests [time × group effect] within the parameter groups; maximal respiratory exchange ratio: RER max , peak oxygen uptake: VO2 peak , oxygen uptake at one watt per kilogram: VO2 1W/kg , maximal power output: PO max , power output at the second lactate threshold: PO LT2 , heart rate at one watt per kilogram: HR 1W/kg , maximal muscular strength: F max for the exercises elbow extension and flexion/knee extension and flexion, total hemoglobin mass: tHb, blood volume: BV, fat mass: FM, fat free mass: FFM).…”
Section: Effects Of Rth On Muscle Strength Capacitysupporting
confidence: 60%
“…Additionally, previous studies that have investigated a lowload RTH (e.g., de Smet et al, 2017;5 week intervention period, 3x/week, loads 20 to 25% of the 1RM) found no superior effect in comparison to a similarly designed resistance training under normoxia on the VO2 peak in young people. In contrast, the study by Álvarez-Herms et al (2016) found a significant improvement in anaerobic performance (+ 53.8% for the total number of sets at 90% of the 300-m "all-out" test).…”
Section: Effects Of Rth On Cardiopulmonary Capacity As Well As the Symentioning
confidence: 77%
See 2 more Smart Citations
“…Previous reports have examined peripheral and cerebral oxygenation with NIRS during repeated sprint exercise, however, none of these studies have been performed with repeated sprint exercise to exhaustion in hypoxic conditions [series of repeated sprints, (Racinais et al, 2007 ; Smith and Billaut, 2010 , 2012 ; Billaut and Buchheit, 2013 ); or incremental ramp test to exhaustion, (Amann et al, 2007 ; Subudhi et al, 2007 )]. In addition, recent research has eluded that there may be greater blood volume shifts in the muscle during repeated sprint exercise possibly due to greater arteriolar dilation together with increased capillary volume (De Smet et al, 2017 ). Therefore, there are factors contributing to the end of exercise within maximal repeated sprints to exhaustion which remain unknown.…”
Section: Introductionmentioning
confidence: 99%